2023
DOI: 10.1111/jpy.13359
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast genome evolution and phylogeny of the early‐diverging charophycean green algae with a focus on the Klebsormidiophyceae and Streptofilum

Sarah E. Glass,
Richard M. McCourt,
Stephen D. Gottschalk
et al.

Abstract: The Klebsormidiophyceae are a class of green microalgae observed globally in both freshwater and terrestrial habitats. Morphology‐based classification schemes of this class have been shown to be inadequate due to the simple morphology of these algae, the tendency of morphology to vary in culture versus field conditions, and rampant morphological homoplasy. Molecular studies revealing cryptic diversity have renewed interest in this group. We sequenced the complete chloroplast genomes of a broad series of taxa s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Our analyses generally found streptophytes to form a pectinate tree with Mesostigma and Chlorokybus forming a monophyletic group. Klebsormidiophyceae are the next major group in our analyses, but Glass et al . (2023) found Interfilum to form a clade branching before the Klebsormidiophyceae.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Our analyses generally found streptophytes to form a pectinate tree with Mesostigma and Chlorokybus forming a monophyletic group. Klebsormidiophyceae are the next major group in our analyses, but Glass et al . (2023) found Interfilum to form a clade branching before the Klebsormidiophyceae.…”
Section: Discussionmentioning
confidence: 80%
“…2014; Graham 1993). Since then, separate phylogenetic analyses using a combination of plastid, mitochondrial, and nuclear genes have recovered support for each clade being the true sister taxon (Glass et al . 2023; Finet et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phylogeny built from a combination of the nuclear 18S rRNA and the plastidial rbcL genes suggested that S. capillatum represents a deep separate streptophyte lineage, even possibly sister to all other streptophytes combined 1 . More recently, Glass et al 2 sequenced the plastid genome of S. capillatum and corroborated its separate phylogenetic status by analyzing a set of 44 plastid-encoded proteins, placing the alga with full support sister to nearly all other streptophytes combined except for the more basally positioned genera Mesostigma and Chlorokybus . From this perspective, the results of the phylotranscriptomic analysis reported by Bierenbroodspot et al 3 are highly surprising: having S. capillatum positioned within Klebsormidiophyceae in a tight clade together with representatives of the genus Interfilum (even making the genus paraphyletic), their tree separates the alga from the position implied by the plastid genes-based phylogeny by five fully supported nodes.…”
mentioning
confidence: 97%
“…Their seemingly well-studied phylogenetic diversity was recently enriched by the discovery of Streptofilum capillaum , a simple filamentous alga forming a novel deep streptophyte lineage in a two-gene phylogeny 1 . A subsequent phylogenetic analysis of plastid genome-encoded proteins resolved Streptofilum as a sister group of nearly all known streptophytes, including Klebsormidiophyceae and Phragmoplastophyta (Charophyceae, Coleochaetophyceae, Zygnematophyceae, and embryophytes) 2 . In a stark contrast, another recent report, published in Current Biology by Bierenbroodspot et al 3 , presented a phylogenetic analysis of 845 nuclear loci resolving S. capillatum as a member of Klebsormidiophyceae, nested among species of the genus Interfilum .…”
mentioning
confidence: 99%